Vertical incidence lithium niobate grating coupler based on random structure grating and preparation method
By using random structure grating and gradient descent algorithm optimization in lithium niobate grating coupler, an efficient vertical incident design is achieved, which solves the problems of low coupling efficiency and difficulty in packaging testing in the existing technology, and achieves efficient grating coupling effect and good scalability.
Patent Information
- Application Number
- CN202411402035.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-24
AI Technical Summary
The existing lithium niobate grating couplers have low coupling efficiency and require tilt incident to improve coupling efficiency, affecting the rear-channel packaging and testing.
The vertical incident lithium niobate grating coupler design is adopted based on random structure gratings, including random structure gratings at incident and exit ends, straight waveguides and conical waveguides. The grating structural parameters are optimized through gradient descent algorithm, combined with microwave plasma surface oxygen plasma Modification, electron beam lithography and reactive ion beam etching are used to prepare efficient vertical incident grating couplers.
It significantly improves coupling efficiency to -3.18dB, is easy to post-package and test, and has good scalability and CMOS process compatibility, and is suitable for large-scale mass production.
Smart Images

Figure CN119179138A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of integrated optical technology, and in particular to a vertical-incident lithium niobate grating coupler based on a random-structure grating and a preparation method thereof. Background Art
[0002] As electronic chips gradually reach the limit of Moore's Law, optical chips play an increasingly important role in the fields of communications and computers. Optical interconnection and optical coupling are the key parts of the connection between optical fiber and optical chip, and their coupling efficiency deeply restricts and affects the development of optical chips. Since lithium niobate has excellent electro-optical response and has a low loss window in the visible light to near-infrared band, the lithium niobate platform has become a platform with great application prospects for optical chips, so the research on lithium niobate surface grating couplers is crucial.
[0003] Yang Dengcai et al. (patent number: 202110691342.2) designed a high-coupling-efficiency segmented uniform grating coupler based on lithium niobate thin film waveguide, by connecting several segments of uniform gratings with different periods and duty cycles together, and adding an Au reflective layer to improve the coupling efficiency of the lithium niobate grating coupler. Gao Shiming et al. (patent number: 202311273374.6) proposed a polarization-insensitive thin-film lithium niobate apodized grating coupler design method, using a particle swarm algorithm to optimize the grating parameters, determine the duty cycle, duty cycle change rate, etching depth and other key structural parameters, so that both the TE mode and the TM mode meet the Bragg conditions, thereby improving the coupling efficiency of the two modes at the same time.
[0004] Both of the above solutions use the traditional grating structure with period and duty cycle as the control means. Due to the low degree of design freedom, the coupling efficiency of the lithium niobate grating coupler cannot be greatly improved. The coupling efficiency of the lithium niobate grating coupler based on the above structure grating is low, and generally requires oblique incidence to improve its coupling efficiency, which will affect the subsequent packaging and testing. Summary of the invention
[0005] In view of the defects in the prior art, the object of the present invention is to provide a vertical-incidence lithium niobate grating coupler based on a random structure grating and a preparation method thereof.
[0006] The vertical-incidence lithium niobate grating coupler based on random structure grating provided by the present invention comprises: a lithium niobate layer, a buried oxide layer, a silicon substrate, an optical fiber outer cladding, an optical fiber inner core layer and a silicon dioxide upper cladding;
[0007] The lithium niobate layer is composed of a random structure grating at the incident end, a random structure grating at the output end, a straight waveguide, and a tapered waveguide; the random structure grating at the incident end and the random structure grating at the output end are connected to the tapered waveguide, and the tapered waveguide is connected to the straight waveguide;
[0008] The lithium niobate layer is located on the buried oxide layer, the buried oxide layer is located on the silicon substrate, and the silicon dioxide upper cladding layer is located on the lithium niobate layer; the optical fiber outer cladding layer directly surrounds the optical fiber inner core layer, and the optical fiber outer cladding layer and the optical fiber inner core layer are directly connected to the silicon dioxide upper cladding layer.
[0009] Preferably, the random structure grating at the output end and the random structure grating at the incident end are symmetrical about the straight waveguide.
[0010] The method for preparing a vertical-incident lithium niobate grating coupler based on a random structure grating provided by the present invention comprises:
[0011] Step S1: Select an X-cut LNOI substrate with a lithium niobate layer thickness of 600 nm, wet clean the LNOI substrate with acetone and isopropanol, and then use a microwave plasma degumming machine to introduce oxygen and nitrogen to perform surface oxygen plasma modification treatment on the surface of the lithium niobate layer;
[0012] Step S2: depositing a layer of amorphous silicon on the upper surface of the lithium niobate layer to serve as a hard mask for subsequent etching of the lithium niobate;
[0013] Step S3: spin coating a layer of electron beam photoresist on the surface of amorphous silicon, and baking the electron beam photoresist;
[0014] Step S4: performing electron beam exposure in an electron beam lithography device, then developing with a MIBK solution and fixing with an isopropyl alcohol solution, and transferring the designed grating coupler pattern onto an electron beam photoresist film;
[0015] Step S5: performing reactive ion beam etching on the substrate in an etching device to transfer the exposed pattern to the amorphous silicon hard mask;
[0016] Step S6: using argon ions to bombard the substrate surface to transfer the structural pattern from the amorphous silicon hard mask to the lithium niobate film, and controlling the etching depth of the lithium niobate layer by controlling the etching time;
[0017] Step S7: removing the remaining amorphous silicon hard mask by using a water bath wet method;
[0018] Step S8: depositing a layer of silicon dioxide upper cladding on the upper surface of the substrate to obtain a vertical-incidence lithium niobate grating coupler based on a random structure grating.
[0019] Preferably, in step S2, the thickness of the layer of amorphous silicon deposited on the upper surface of the lithium niobate layer is 600 nm.
[0020] Preferably, in step S3, the conditions for baking the electron beam photoresist are: heating the substrate at 150° C. for one minute.
[0021] Preferably, in step S5, the etching rate of amorphous silicon by reactive ion beam etching is 1.62 nm / s, the etching time is 370 s, and the etching depth is 600 nm.
[0022] Preferably, in step S6, the etching rate of lithium niobate etched by argon ions is 1.48 nm / s, the etching time is 270 s, and the etching depth is 400 nm.
[0023] Preferably, in step S7, a potassium hydroxide solution having a concentration of 30% is diluted to 15%, and then treated in a water bath at a temperature of 80° C. for 5 minutes, and then the surface of the substrate is subjected to surface modification treatment using the method in step S1.
[0024] Preferably, in step S8, the thickness of the silicon dioxide upper cladding layer is 2 μm.
[0025] Preferably, after step S8, a test step 9 is also included, using a 1500nm-1600nm band laser, optical fiber, substrate placement table and photodetector to test and obtain the transmittance, calculate the coupling efficiency curve, and thus evaluate the coupler performance.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention designs a vertically incident lithium niobate grating coupler based on a random structure grating based on a gradient descent algorithm with random initial conditions, which greatly reduces the backscattering of the incident light and significantly improves the coupling efficiency, which can be increased to -3.18dB;
[0028] (2) The present invention adopts a completely vertical coupling method, which is easy to package and test later, and the coupling efficiency is the highest among the literature and patents that can be consulted currently;
[0029] (3) The method designed in the present invention for designing a vertical-incident lithium niobate grating coupler based on a random structure grating using a gradient descent algorithm has good scalability and can be extended to the design of other passive optical devices on any optical platform (lithium tantalate platform, etc.);
[0030] (4) The preparation method of the grating coupler in the present invention is compatible with the CMOS process and does not require the introduction of a bottom metal reflector, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0032] Figure 1 It is a schematic diagram of the top view structure of the grating coupler;
[0033] Figure 2 is a schematic diagram of the cross-sectional structure of a grating coupler;
[0034] Figure 3 Schematic diagram of the three-dimensional structure of the grating coupler;
[0035] Figure 4 Flowchart for structural parameter optimization of gradient descent algorithm based on random initial conditions;
[0036] Figure 5 This is a comparison chart of the simulated light coupling efficiency and experimental light coupling efficiency curves of the grating coupler.
[0037] In the figure, 1-random structure grating at the incident end, 2-random structure grating at the output end, 3-straight waveguide, 4-tapered waveguide, 5-lithium niobate layer, 6-buried oxide layer, 7-silicon substrate, 8-optical fiber outer cladding, 9-optical fiber inner core layer, 10-silicon dioxide upper cladding. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0039] Example 1
[0040] The present invention provides a vertical-incidence lithium niobate grating coupler based on a random-structure grating and a preparation method thereof. The vertical-incidence lithium niobate grating coupler based on a random-structure grating is processed on a thin-film lithium niobate substrate, firstly depositing an amorphous silicon thin film, then spin-coating an electron beam photoresist and performing electron beam exposure patterning, etching the amorphous silicon using the photoresist as a mask, then etching the lithium niobate using the amorphous silicon as a hard mask, and cleaning away the residual amorphous silicon and by-products to obtain the grating coupler.
[0041] The vertical-incidence lithium niobate grating coupler based on random structure grating comprises: a random structure grating 1 at the incident end, a random structure grating 2 at the output end, a straight waveguide 3, a tapered waveguide 4, a lithium niobate layer 5, a buried oxide layer 6, a silicon substrate 7, an optical fiber outer cladding 8, an optical fiber inner core layer 9 and a silicon dioxide upper cladding 10;
[0042] Among them, the random structure grating 1 at the incident end, the random structure grating 2 at the output end, the straight waveguide 3, and the tapered waveguide 4 together constitute a lithium niobate layer 5; the lithium niobate layer 5 is located on the buried oxide layer 6, the buried oxide layer 6 is located on the silicon substrate 7, and the silicon dioxide upper cladding 10 is located on the lithium niobate layer 5; the random structure grating 1 at the incident end is connected to the tapered waveguide 4, the tapered waveguide 4 is connected to the straight waveguide 3, and the random structure grating 1 at the incident end and the random structure grating 2 at the output end are symmetrical about the straight waveguide 3; the optical fiber outer cladding 8 is directly surrounded by the optical fiber inner core layer 9, and the optical fiber outer cladding 8 and the optical fiber inner core layer 9 are directly connected to the silicon dioxide upper cladding 10.
[0043] The preparation method of the grating coupler is as follows:
[0044] Step S1, wet cleaning the LNOI substrate with acetone and isopropanol, and then using a microwave plasma stripper (PVA TePlaPlasma Processing System) to introduce oxygen and nitrogen to perform surface oxygen plasma modification treatment on the surface of the lithium niobate layer;
[0045] Step S2, depositing a layer of amorphous silicon on the upper surface of the top lithium niobate as a hard mask for subsequent etching of lithium niobate, with a thickness of 600nm; according to process experience, when amorphous silicon is used as a hard mask for etching lithium niobate in the subsequent process, the etching selectivity ratio of amorphous silicon to lithium niobate is close to 1:1. Since lithium niobate of more than 400nm needs to be etched and an excessively thick amorphous silicon layer is likely to affect etching, 600nm of amorphous silicon is selected to be deposited;
[0046] Step S3, spin coating a layer of 6200.09 electron beam photoresist on the surface of the amorphous silicon, and heating the substrate at 150° C. for one minute to bake the electron beam photoresist; wherein 150° C. is obtained based on the basic process parameters of electron beam photoresist exposure;
[0047] Step S4, performing electron beam exposure in an electron beam lithography device, then developing with a MIBK solution and fixing with an isopropyl alcohol solution, and transferring the designed grating coupler pattern onto an electron beam photoresist film;
[0048] Step S5, performing reactive ion beam etching on the substrate in an etching device to transfer the exposed pattern to an amorphous silicon hard mask;
[0049] Step S6, bombarding the substrate surface with argon ions to transfer the structural pattern from the amorphous silicon hard mask to the lithium niobate layer film, and controlling the etching depth of the lithium niobate layer by controlling the etching time;
[0050] Step S7, using a water bath wet method to remove the remaining amorphous silicon hard mask; specifically: using a potassium hydroxide (KOH) solution with a concentration of 30%, diluting it to 15%, treating it in a water bath at a temperature of 80° C. for 5 minutes, and then using the method in step S1 to perform surface modification treatment on the surface of the substrate;
[0051] Step S8, depositing a 2 μm thick silicon dioxide upper cladding layer on the upper surface of the substrate to obtain a vertical-incidence lithium niobate grating coupler based on a random structure grating.
[0052] In step S5, the etching time is 370 seconds and the etching depth is 600 nm. The etching rate of amorphous silicon using reactive ion beam etching is about 1.62 nm / s. In order to etch through 600 nm of amorphous silicon, an etching time of 370 seconds is required.
[0053] In step S6, the etching time is 270 seconds and the etching depth is 400 nm. The etching rate of lithium niobate by argon ion etching is about 1.48 nm / s. In order to achieve a lithium niobate etching depth of 400 nm, an etching time of 270 seconds is required.
[0054] After step S8, a test step 9 is also included, using a 1500-1600nm band laser, an optical fiber, a substrate placement table and a photodetector to test the transmittance and calculate the coupling efficiency curve, thereby evaluating the coupler performance.
[0055] Example 2
[0056] Based on the existing lithium niobate grating coupler structure, the present invention uses a gradient descent algorithm to optimize a random grating structure with high coupling efficiency (such as Figure 1 As shown), the light in the optical fiber is vertically incident on the surface of the lithium niobate layer grating, (as shown Figure 2 and Figure 3 The gradient descent algorithm is as follows: the L-BFGS-BB (Limited-memory Broyden-Fletcher-Goldfarb-Shanno) algorithm is used for optimization until the number of iterations exceeds 200 or the FOM change is less than 10. -5 , thereby optimizing the final grating structure parameters.
[0057] This example also provides a method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating, comprising the following steps: step S1, wet-cleaning the LNOI substrate with acetone and isopropanol in sequence, and then performing surface oxygen plasma modification treatment on the top lithium niobate surface; step S2, depositing a layer of amorphous silicon on the top lithium niobate surface as a hard mask for subsequent etching of the lithium niobate, with a thickness of 600nm; step S3, spin-coating a layer of 6200.09 electron beam photoresist on the amorphous silicon surface, and heating the substrate at 150°C for one minute to bake the electron beam photoresist; step S4, performing electron beam exposure in an electron beam lithography device, and then using a MIBK solution to Develop, fix with isopropyl alcohol solution, transfer the designed grating coupler layout to the electron beam photoresist film; step S5, perform reactive ion beam etching on the substrate in an etching device, and transfer the exposed pattern to the amorphous silicon hard mask; step S6, bombard the substrate surface with argon ions, transfer the structural pattern from the amorphous silicon hard mask to the lithium niobate layer film, and control the etching depth of the lithium niobate layer by controlling the etching time; step S7, use a water bath wet method to remove the residual amorphous silicon hard mask and by-products; step S8, deposit a 2μm thick silicon dioxide upper cladding layer on the upper surface of the substrate to obtain a vertical incidence lithium niobate grating coupler based on a random structure grating.
[0058] Embodiment 3:
[0059] The implementation process is the same as Example 2 except for the following differences.
[0060] like Figure 4 As shown in Example 1, we use a grating based on a random initial structure. Before using the gradient descent algorithm for optimization, we first use the loop algorithm to find a set of random initial structure gratings with the highest coupling efficiency among 1000 random initial conditions. Then, a set of random structure gratings is optimized based on the gradient descent algorithm, and then the FDTD software is used to optimize the thickness of the silicon dioxide upper cladding. The preparation process is the same as shown in Example 1. Then the coupling efficiency of the coupler is obtained by testing on the test bench (such as Figure 5 As shown in Figure 2, it can be found that the experimental result curve is consistent with the FDTD simulation curve, and the experimental coupling efficiency reaches -3.18dB. It can be seen that the random structure grating optimized based on the gradient descent algorithm greatly improves the coupling efficiency of the lithium niobate grating coupler.
[0061] Those skilled in the art know that, in addition to implementing the system, device and its various modules provided by the present invention in a purely computer-readable program code, it is entirely possible to implement the same program in the form of logic gates, switches, application-specific integrated circuits, programmable logic controllers and embedded microcontrollers by logically programming the method steps. Therefore, the system, device and its various modules provided by the present invention can be considered as a hardware component, and the modules included therein for implementing various programs can also be considered as structures within the hardware component; the modules for implementing various functions can also be considered as both software programs for implementing the method and structures within the hardware component.
[0062] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.
Claims
1. A vertical-incidence lithium niobate grating coupler based on a random structure grating, characterized in that: include: A lithium niobate layer (5), a buried oxide layer (6), a silicon substrate (7), an optical fiber outer cladding (8), an optical fiber inner core layer (9) and a silicon dioxide upper cladding (10); The lithium niobate layer (5) is composed of an incident end random structure grating (1), an output end random structure grating (2), a straight waveguide (3), and a tapered waveguide (4); the incident end random structure grating (1) and the output end random structure grating (2) are connected to the tapered waveguide (4), and the tapered waveguide (4) is connected to the straight waveguide (3); The lithium niobate layer (5) is located on the buried oxide layer (6), the buried oxide layer (6) is located on the silicon substrate (7), and the silicon dioxide upper cladding layer (10) is located on the lithium niobate layer (5); the optical fiber outer cladding layer (8) directly surrounds the optical fiber inner core layer (9), and the optical fiber outer cladding layer (8) and the optical fiber inner core layer (9) are directly connected to the silicon dioxide upper cladding layer (10).
2. The vertical-incidence lithium niobate grating coupler based on random structure grating according to claim 1, characterized in that: The incident end random structure grating (1) and the output end random structure grating (2) are symmetrical about the straight waveguide (3).
3. A method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating as claimed in claim 1 or 2, characterized in that: include: Step S1: wet-cleaning the LNOI substrate with acetone and isopropanol in turn, and then using a microwave plasma degumming machine to introduce oxygen and nitrogen to perform surface oxygen plasma modification treatment on the surface of the lithium niobate layer; Step S2: depositing a layer of amorphous silicon on the upper surface of the lithium niobate layer to serve as a hard mask for subsequent etching of the lithium niobate; Step S3: spin coating a layer of electron beam photoresist on the surface of amorphous silicon, and baking the electron beam photoresist; Step S4: performing electron beam exposure in an electron beam lithography device, then developing with a MIBK solution and fixing with an isopropyl alcohol solution, and transferring the designed grating coupler pattern onto an electron beam photoresist film; Step S5: performing reactive ion beam etching on the substrate in an etching device to transfer the exposed pattern to the amorphous silicon hard mask; Step S6: using argon ions to bombard the substrate surface to transfer the structural pattern from the amorphous silicon hard mask to the lithium niobate film, and controlling the etching depth of the lithium niobate layer by controlling the etching time; Step S7: removing the remaining amorphous silicon hard mask and byproducts by using a water bath wet method; Step S8: depositing a layer of silicon dioxide upper cladding on the upper surface of the substrate to obtain a vertical-incidence lithium niobate grating coupler based on a random structure grating.
4. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: In step S2, a layer of amorphous silicon is deposited on the upper surface of the lithium niobate layer with a thickness of 600 nm.
5. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: In step S3, the electron beam photoresist is baked under the following conditions: the substrate is heated at 150° C. for one minute.
6. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: In step S5, the etching rate of amorphous silicon is 1.62 nm / s, the etching time is 370 s, and the etching depth is 600 nm.
7. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: In step S6, the etching rate of lithium niobate by argon ion etching is 1.48 nm / s, the etching time is 270 s, and the etching depth is 400 nm.
8. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: In step S7, a potassium hydroxide solution with a concentration of 30% is diluted to 15%, and then treated in a water bath at a temperature of 80° C. for 5 minutes. Then, the substrate is surface modified using the method in step S1.
9. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: In step S8, the thickness of the silicon dioxide upper cladding layer is 2 μm.
10. The method for preparing a vertical-incidence lithium niobate grating coupler based on a random structure grating according to claim 3, characterized in that: After step S8, a test step 9 is also included, using a 1500nm-1600nm band laser, an optical fiber, a substrate placement table and a photodetector to test and obtain the transmittance, and calculate the coupling efficiency curve to evaluate the coupler performance.
